PENGARUH COPRORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri dasar dan kimia yang terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Setyowati, 15.05.52.0327; Poerwati, Tjahjaning (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of Corporate Social Responsibility, Good Corporate Governance is proxied by independent commissioners and audit committees, profitability to the value of companies listed on the Indonesia Stock Exchange for the period 2015-2017. The sample in this study is a basic industrial and chemical manufacturing company listed on the Indonesia Stock Exchange for the period 2015-2017 using purposive sampling. The analytical method used is multiple linear regression analysis. Based on the results of data processing, it was found that the disclosure of corporate social responbility (CSR) variables was statistically significant positive effect on firm value. GCG proxied by independent commissioners statistically has a negative effect not significantly on Corporate Value while GCG proxied by the Audit Committee has a significant positive effect on Corporate Values and Profitability variables have a significant negative not significantly effect on firm value.